(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In contemporary education, the development of foreign language teachers’ professional competence has become one of the priority areas of pedagogical research. Modern educational approaches require teachers not only to possess strong linguistic knowledge but also to demonstrate methodological literacy, communicative competence, and innovative thinking. Therefore, methodological culture is considered an essential component of professional teacher development, as it integrates pedagogical, psychological, and linguistic competencies into a unified system. The modernization of foreign language education emphasizes the importance of communicative approaches, innovative teaching technologies, and learner-centered instruction. In this regard, the formation of methodological mastery, creativity, and research competence plays a significant role in improving the quality of foreign language teaching. This article examines the theoretical foundations of methodological culture and analyzes its role in the development of teachers’ professional competence.